Microstructure, Physical-Mechanical, and Magnetic Characteristics of a Butt-Welded Joint Obtained by Rotary Friction Welding Technology of Bimetallic Pipe - Evgeniia Putilova; Kristina Kryucheva; Ivan Kamantsev; Elena Priymak (Journal of Manufacturing and Materials Processing)
The development of technology, including in the oil and gas industry, necessitates the creation of materials with special sets of properties, such as high strength characteristics combined with corrosion resistance. One such material is bimetallic pipe, but we are faced with the problem of creating extended structures and obtaining high-quality butt-welded joints of such industrial bimetallic pipes. The microstructure in different parts of the thermomechanically influenced zone of a butt-welded joint of a bimetallic pipe obtained by rotary friction welding (RFW) was investigated by optical and electron microscopy methods. It was established that during rotary friction welding of the bimetallic pipe in standard mode, one metal flowed into the zone of another. This could be explained by the different plastic properties of the steels that made up the bimetal, which must be taken into account in future welding. Standard RFW mode did not result in the formation of a high-quality weld; defects and discontinuities were observed in the joint area. The maximum hardness values were observed directly in the weld joint. It is concluded that rotary friction welding can be used as a welding technology for bimetallic pipes, but the most attention should be paid to the welding mode to obtain a high-quality butt-welded joint.